Hypertrophy of the external and sphincter in haemorrhoids: a histometric study. Issue 1 (January 1981) - Teramoto, T; Parks, A G; Swash, M
Abstract : Biopsies of the external and sphincter taken from 24 male patients with haemorrhoids were subjected to examination using histochemical techniques. Fibre size (type 1 mean: 33 micrometers +/- 11.0 SD and type 2 mean: 47.9 micrometers +/- 15.0 SD) was increased when compared with control subjects. The distribution of muscle fibre types in these patients showed markedly greater type 1 fibre predominance (92%) than in control subjects. These abnormalities of the external sphincter did not show any clear relationship with age, degree of haemorrhoidal change, length of history of haemorrhoids, history of straining or of constipation, or perineal descent; however, increasing length of history up to 10 years was associated with increasing type 1 fibre predominance. We suggest that the external and sphincter in patients with haemorrhoids is in a state of increase tonic contraction, which causes work induced muscle hypertrophy and may contribute to increased resting pressure in the anal canal in patients with haemorrhoids.